Xanthochromia revisited: a re-evaluation of lumbar puncture and CT scanning in the diagnosis of subarachnoid haemorrhage. Issue 3 (March 1988) - MacDonald, A; Mendelow, A D
Abstract : The CT and cerebrospinal fluid (CSF) findings of 100 patients with ruptured intracranial aneurysms were reviewed. Forty six percent of the 68 patients who had a lumbar puncture had blood stained CSF but with no xanthochromia. There was no blood visible on the CT scan in 20 patients: seven of these 20 had blood in their CSF, but no xanthochromia. It is concluded that it is blood stained CSF that is important in the diagnosis of subarachnoid haemorrhage (SAH), and not xanthochromia, and that a normal CT scan (EMI 1010) and the absence of xanthochromia in the CSF do not exclude a ruptured intracranial aneurysm. To diagnose SAH, it may be necessary to perform both investigations; the CT scan as the primary investigation in those patients in whom lumbar puncture is judged to be hazardous; the lumbar puncture as the secondary investigation in those patients with a normal CT scan.